Orbitopalpebral emphysema in a child after the removal of a giant meningioma: a case report and mini-review - Ebba Katsler; Anders Tolstrup Christiansen; Annika Reynberg Langkilde; Jane Skjøth-Rasmussen (Brain and Spine)
Research question: to describe and investigate the case of an 11-year-old boy with the concomitant pneumocephalus, subcutaneous- and orbitopalpebral emphysema after the removal of a giant meningioma. Furthermore, our aim is to discuss the findings and the pathophysiology in relation to cases found in literature. Material and methods: We performed a search in PubMed, Cochrane, MEDLINE and Google Scholar by the usage of the words orbital or periorbital, combined with emphysema and neurosurgery. In addition, a manual search was performed from reference lists. Results: In the absence of a trauma and fracture in the orbit, it is considered extremely rare with the simultaneous presentation of an orbital emphysema and pneumocephalus. The literature search revealed 1101 results, with four cases of the simultaneous presentation of orbital emphysema and pneumocephalus after a neurosurgical procedure. Our case of an orbitopalpebral emphysema and pneumocephalus following the removal of a giant meningioma is unique. Discussion and conclusion: Orbital emphysema might give rise to orbital compartment syndrome, an ophthalmologic emergency, that untreated can result in blindness. Differentiating orbitopalpebral emphysema from postoperative swelling can be accomplished through palpation, which might reveal crepitations, and via an acute CT scan that highlights the presence of air.Following a neurosurgical procedure, orbital emphysema is an extremely rare phenomenon. Given the rarity of this case, we present informed assumptions and propose a bidirectional migration of air: from intracranial space, to the orbit and subcutaneously to the palpebrae.